Resgate, caracterização morfométrica e avaliação bromatológica de acessos de Stylosanthes Sp. do semiárido baiano - Santana, Andréa dos Santos (2010)
The work let than to be redeemed natural populations of the genus Stylo-Santha and constituted active germplasm banks of UEFS and UNEB. Through two precedente routes in Regions Sisal and shallow middle San Francisco where they were ranson 81 hits in 91 georeferenced points with the assistance Global Positioning System (GPS). We identified species: Stylosanthes angustifolia, S. capitata, S. guianensis, S. macrocephala, S. pilosa, S. scabra and S. viscous. Parts of these accessions collected were propagated and characterized morphometrically with the use of descriptors. Significant differences were detected between populations of diferente species. Within each population of the same species not found a statistically significant only for the population of S. pilosa, all species showed significant diferences within the populations of the same species. The characters that contributed most to this differentiation in most species studied were: height of plant (ALP), stem diameter plant (DCP) and petiole length (PE). The populations of S. scabra and S. macrocephala were more distinct in discriminant analysis. For the analysis of main components, the species S. pilosa and S. viscosa had more than 80% of its variability explained in the first three principal components. There has been investigating the nutritional content of 28 accessions of Stylosanthes from the region of shallow middle San Francisco, through, the statistical package SISVAR, and evaluated the possible differences between species of the genus Stylosanthes. Only the percentage of crude protein, has presented a significant difference at 5%. Concentrations found in the shows, meet the needs of goats and sheep from the young women, according to the National Research Council (1985). When comparing the averages of the components of nutrition of the genus Stylosanthes with averages out various types of pulses of the caatinga, it was observed that the averages found for the genre of the genus Stylosanthes was more than a reasonable amount of formiddlings caatinga.